PERANAN KEPOLISIAN DALAM MENCEGAH TINDAK PIDANA PEMERASAN YANG DILAKUKAN OLEH PREMAN DI WILAYAH HUKUM KEPOLISIAN SEKTOR KOTA PEKANBARU - Bayu Sugara; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Extortion is a criminal offense that is often done by a thug who is usually a disease of society. The criminal act of extortion should be prevented and eradicated because of it is impacts makes comfort and disturbed public tranquility. Police as a state apparatus that perform the function of law enforcement, custodians, security, and public order and the protection, shelter, and serve the community. The police on duty to prevent and combat the crime of extortion. The purpose of this thesis, that is: first, the role of municipal the city police of Pekanbaru in preventing criminal acts of extortion committed by thugs, second, obstacles faced by the city police of Pekanbaru in preventing criminal acts of extortion committed by thugs, third, the efforts of the municipal the city police of Pekanbaru in prevent the crime of extortion carried out by thugs pliers.This research is a sociological study, this study was conducted in eleven police of Pekanbaru sector, while the overall population and the sample is related to the overall problems examined in this study. Source of data used is primary data, secondary data, and tertiary data. Data collection techniques in this study were interviews, questionnaire and literature study and data analysis technique used is by a qualitative way.Out of the results of research can be concluded, first, the role the police city of Pekanbaru in preventing the crime of extortion committed by a thug with first requests that preventive action (non-penal), pre-emptive, and repressive. Second, barriers, faced the police city of Pekanbaru in preventing the crime of extortion committed by thugs in the police city of Pekanbaru include: a lack of information from the public, the lack of human resources Polri, lack of public awareness, victims who did no report. Third, the efforts of the police city of Pekanbaru sector to prevent acts of thuggery and extortion committed by thugs include: providing information and knowledge to the public to danger of acts thuggery and extortion committed by thugs, the efforts of police to foster good relationship to the society. Advice writer, first, the police city of Pekanbaru sector in realizing it is role as the prevention and eradication of the crime of extortion should be more consistent in carrying out it is role both in action, preventive, pre-emptive, repressive. Second, to overcome barriers to the prevention and eradication of the crime of extortion need to collaborate and embrace the community, improve facilities and infrastructure. Thirdly, the police city of Pekanbaru must strive to increase the prevention of acts of thuggery and extortion committed by thugs so that action can eradicate thuggery.Keywords: Character-The Police city of Pekanbaru sector-Prevention-Extortion